PENINGKATAN KAPASITAS IBU BALITA MELALUI KELAS IBU BALITA PLUS COPING SKILL TRAINING UNTUK PENCEGAHAN STUNTING DI KELURAHAN KEDUNG KELOR, TEGAL - Runjati Runjati; Triana Sri Hardjanti; Shinta Dhian Hasna’ Atifah; Nur Abadi (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2025)
Stunting is a chronic nutritional problem that affects children’s physical growth, cognitive development, and long-term quality of life. Prevention efforts require integrated interventions, including nutrition education and the strengthening of emotional management skills for mothers of children under five. This community service program aims to improve mothers’ knowledge through mother classes combined with coping skill training (CST) as a strategy to monitor child growth and detect stunting early. The program was implemented through several stages: planning, coordination with posyandu cadres, pretest-Posttets, health education using leaflets, posttest, data analysis, and evaluation. The participants were mothers of children under five at Posyandu Mawar Merah, Kedungkelor Village, Warurejo District, Tegal Regency. The results showed an increase in knowledge among 29 respondents, while 1 respondent experienced a decrease, with a statistically significant difference between pretest and posttest scores (p = 0.000; p < 0.05). These findings demonstrate that enhancing the capacity of mothers with toddlers through the Toddler Mothers Class combined with coping skill training for stunting prevention in Kedung Kelor, Tegal is effective in improving mothers’ knowledge of emotional management in monitoring child growth and development for stunting prevention. The program is recommended to be further developed with varied counseling methods to enhance sustainability and effectiveness.